The Effect of Body Mass Index of Patients with Post Myocardial Infarction Angina on the Heart Function - Hassan, Hakemia Sh. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Extreme obesity is recognized to be a risk factor for coronary heart disease. It is unclear whether overweight and normal weight also poses a risk. Objective: The study aims to determine the effect of the body mass index on coronary arteries and left ventricular functions in patients with post myocardial infarction (MI) angina Method: The study included 50 patients with the diagnosis of post MI angina consecutively admitted to the medical ward of Iraqi Center for Heart Disease. All patients underwent coronary artery catheterization and Echocardiography for assessment of coronary artery and left ventricular functions Results: The results of the study showed that there is a significant difference in impaired left ventricular systolic pressure between normal weight and overweight patients with post MI angina .The study also revealed that (16.16%) of the patients with normal weight and (30.76%) of the patients who are over weight had three vessels disease. Conclusion: left ventricular functions reflected by ejection fraction and left ventricular wall motion and state of coronary artery were better in normal weight patients than in over weight patients.